2018
DOI: 10.1111/jen.12540
|View full text |Cite
|
Sign up to set email alerts
|

Sugar preferences of western corn rootworm larvae in a feeding stimulant blend

Abstract: Feeding behaviour, feeding intensity and staying behaviour of neonate western corn rootworm larvae (Diabrotica virgifera virgifera LeConte) were evaluated in response to synthetic feeding stimulant blends to determine larval preferences among the three maize root sugars (glucose, fructose and sucrose) in the active blend and to determine whether any single sugar can substitute for the 3‐sugar combination in a feeding stimulant blend. These experiments demonstrated the strong affinity that western corn rootworm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…2D). Responsiveness to non-volatile attractants, Fe(III)(DIMBOA) 3 and a blend of glucose, fructose and sucrose (Bernklau et al, 2018b;Hu et al, 2018) was also unaltered in DvvGr2-silenced larvae (Figs 2E, F), demonstrating that knocking down DvvGr2 expression does not alter the capacity of WCR larvae to respond to other important chemical cues. Second, we assessed the contribution of DvvGr2 to CO2 responsiveness using synthetic CO 2 at different concentrations (Fig.…”
Section: Dvvgr2 Expression Is Specifically Required For Behavioural Rmentioning
confidence: 91%
See 3 more Smart Citations
“…2D). Responsiveness to non-volatile attractants, Fe(III)(DIMBOA) 3 and a blend of glucose, fructose and sucrose (Bernklau et al, 2018b;Hu et al, 2018) was also unaltered in DvvGr2-silenced larvae (Figs 2E, F), demonstrating that knocking down DvvGr2 expression does not alter the capacity of WCR larvae to respond to other important chemical cues. Second, we assessed the contribution of DvvGr2 to CO2 responsiveness using synthetic CO 2 at different concentrations (Fig.…”
Section: Dvvgr2 Expression Is Specifically Required For Behavioural Rmentioning
confidence: 91%
“…To investigate larval responses to non-volatile root chemicals, we tested two well established attractants, Fe(III)(DIMBOA) 3 and a sugar blend (Bernklau et al, 2018b;Hu et al, 2018). To evaluate the attractive effects of Fe(III)(DIMBOA)3, we released six 2 nd -3 rd instar WCR larvae in the middle of a moist sand-filled Petri plate (6 cm diameter, Greiner Bio-One GmbH, Frickenhausen, DE) where they had a choice between a filter paper disc treated with 10 μl of Fe(III)(DIMBOA) 3 (1 µg/ml of water) or, on the opposite side, a filter paper disc treated with water only.…”
Section: Insect Behavioural Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugar is phagostimulant for house flies, however, with development of taste aversion-related behavioral resistance in house fly (Burgess and King, 2017), high caloric sweeteners have been suggested for inclusion in baits against house fly (Fisher et al, 2017). Corn syrup is another alternative to replace low caloric sugar (Bernklau et al, 2018), and its phagostimulant property is not well established. Studies with other sugary materials have demonstrated differences in effectiveness in baits, like solutions of molasses that were more attractive to house flies than honey, maple syrup, or jaggery (date palm sugar) (Geden et al, 2009).…”
Section: Introductionmentioning
confidence: 99%